ANALISIS RASIO KEUANGAN DALAM MENGUKUR KINERJA PERUSAHAAN PADA PT. ASKRINDO DI KOTA MAKASSAR - Mardiana Ibrahim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
Today, insurance has evolved into a line of business or business interest and has no role in the economic life and in development, especially in the field of finance. PT. Askrindo an insurance or general insurance where the insurance is a banking partner in terms of co closing or warrant the risks that may be experienced by the customers of the bank is to guarantee losses on the occurrence of a credit risk against collateral, such as the risks of fire, theft, robbery, accidents and other